The Role of Teachers in Realizing the Vision of Modern Islamic Education - Afiful Ikhwan (JIE (Journal of Islamic Education), 2024)
The vision of Islamic education in the 21st century focuses on creating individuals who are faithful, knowledgeable, morally upright (akhlaqul karimah), and capable of facing global challenges. In this context, the role of teachers is crucial as value transmitters and guides for a quality generation. This article aims to examine the impact of the 21st-century Islamic education vision on the role of teachers and to identify the challenges while reinforcing their position in education. Using a descriptive qualitative method, the study explores 21st-century Islamic education at PAS Baitul Qur’an and finds that today’s teachers must not only master Islamic knowledge but also possess technological skills, creative teaching methods, and the ability to foster students' character development. Some challenges include a lack of training, shifts in learning approaches, and limited institutional support. Therefore, strategies to strengthen the teacher's role should involve professional development, spiritual reinforcement, and collaboration between schools and the government.